First report of Rice stripe necrosis virus infecting rice in Sierra Leone - Tucker, M.J. (2020)
While Rice stripe necrosis virus (RSNV, Benyvirus, Benyviridae) has been reported on rice plants on two continents, little is known about the diversity of this multipartite virus which is transmitted by the plasmodiophorid protist Polymyxa graminis. First identified in 1983 in the Côte d'Ivoire (Fauquet & Thouvenel, 2), the disease had previously been observed in Sierra Leone without formal identification of the causal agent (Buddenhagen, pers. comm.). Later, the virus was reported in South and Central America (Colombia, Ecuador, Panama and Brazil) causing up to 40% yield losses (Morales et al., 4). Recently, RSNV was identified for the first time in several African countries including Burkina Faso (Sérémé et al., 6), Benin (Oludare et al., 5) and Mali (Decroës et al., 1) suggesting a re-emergence of the virus in Africa.